Not Sweet: Glucocorticoids from Intratumoral Myeloid Cells Disable T Cells - Effern, Maike; Hölzel, Michael (Immunity (Cambridge, Mass.), 2020)
In this issue, Acharya et al. demonstrate that glucocorticoids produced by macrophages and monocytes in the tumor microenvironment induce a dysfunctional CD8 T cell phenotype. Blocking myeloid glucocorticogenesis enhances tumor immune surveillance and responsiveness to immune checkpoint therapy.